Patterns of prescription of psychotropic drugs on inpatients with schizophrenia and related disorders at Víctor Larco Herrera Hospital 2015 - Bojórquez Giraldo, Enrique (2018)
Introduction. Antipsychotics are the base of therapeutic in schizophrenia; in its prescription potential benefits and risks should be assessed. Objective. Identify patterns of prescription of psychoactive drugs in patients diagnosed with schizophrenia and related disorders. Design. Observational, descriptive, longitudinal, retrospective. Setting. Víctor Larco Herrera Hospital. Participants. Patients with diagnosis of F2 category (ICD-10); older than18 years of age, with a minimum stay of 15 days and admitted in 2015. Interventions. The medical records were evaluated and the data was collected in a datasheet, which were later poured into a Microsoft Excel 2010 database and analyzed. Main outcome measures. Patterns of prescription. Results. We reviewed 174 medical records. The most frequent diagnosis was schizophrenia (72.4%). The prescription was grouped into three stages: Start of treatment (first 14 days), course of treatment (15 days onwards) and hospital discharge. The most commonly used antipsychotic was risperidone. The change in antipsychotics was greater at the start of treatment (59.2%). Simultaneous use of antipsychotics was 57% at start of the treatment and subsequently reduced. The most frequent combination was oral antipsychotics and depot (25-40%). Other psychotropic drugs used were benzodiazepines (60-80%), mood stabilizers (50%), and anticholinergics (50%). The average number of medications prescribed during hospitalization was 4.74. Conclusions. The prescription pattern found was polypharmacy, associated with the simultaneous use of antipsychotics and / or adjuvant medication.